High-efficiency water splitting catalyzed by NiMoO4 nanorod arrays decorated with vacancy defect-rich NiTex and MoOy layers. (20th January 2023) - Xu, Wentao; Wu, Kefeng; Wu, Yanhua; Guo, Qian; Fan, Fangfang; Li, Anmei; Yang, Linjuan; Zheng, Fuqin; Fan, Youjun; Chen, Wei
Abstract: Nickel molybdate is a promising non-noble metal candidate for alkaline hydrogen evolution reaction (HER), but its insufficient activity due to its low conductivity and slow reaction kinetics hinders its application for large-scale commercial hydrogen production. Here, we report an efficient self-supporting electrocatalyst consisting of NiMoO4 nanorods modified by MoOy with abundant internal oxygen vacancies and epitaxially grown NiTex with high specific surface area for alkaline HER. Benefiting from the structural advantages of nanorods/nanosheets integrated electrode, a larger specific surface area and abundant active centers can be provided for the HER. Such constructed NiTex /MoOy /NiMoO4 catalyst achieves a low overpotential of 59 mV to drive a current density of 10 mA cm −2 and a low Tafel slope of 32.8 mV dec −1 in 1.0 M KOH solution with sustainable durability. Additionally, a two-electrode electrolytic cell system assembled with NiTex /MoOy /NiMoO4 and NiMoO4 employed as cathode and anode, respectively, extraordinary performance with a voltage of 1.49 V at a current density of 10 mA cm −2 was achieved in alkaline electrolyte. This work demonstrates a novel idea for metalloid Te-modified transition metal oxides, which is expected to expand the family of stable and efficient transition metal oxide (such as CoMoO4, Co3 O4, NiCo2 O4, etc.)-based catalysts for energy electrocatalysis. Graphical abstract: Image, graphical abstract